(untitled) (Eduscotech, 2024)
This study aims to describe the integration of civic values into digital learning planning and its impact on enhancing elementary school students’ democratic literacy. A descriptive qualitative approach with a case study design was employed. The research was conducted at SDN Sugihwaras 3, Magetan Regency, involving one fifth-grade teacher, one principal, and six students as informants. Data were collected through interviews, observations, documentation, and questionnaires. The findings revealed that the teacher successfully incorporated democratic values such as tolerance, deliberation, and responsibility into digital lesson plans using interactive digital media. Students demonstrated improved participation, critical thinking, and respect for differences after engaging in the learning process. The presence of adequate digital infrastructure and supportive school policies contributed to the success of the implementation. This study concludes that digital learning planning integrated with civic values can effectively and contextually enhance students’ democratic literacy. Further research is recommended to explore similar practices across different educational levels and settings.